L’efficacité d’images de la série sur l'enseignement de l'écriture des étudiants du semestre II dans La section de la pédagogie de français - Uchi Mely Viani; Dwi Astuti (Universitas Negeri Semarang, 2024)
The purpose of this study was to test the effectiveness of the use of serial image carriers in writing for students in the second semester of the French Language Education Program. The research method used in this study was a